2015
DOI: 10.1016/j.bbamem.2015.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of bacterial sensitivity and resistance to mammalian Group IIA phospholipase A2

Abstract: Group IIA secretory phospholipase A2 (sPLA2-IIA) of mammalian species is unique among the many structurally and functionally related mammalian sPLA2 in their high net positive charge and potent (nM) antibacterial activity. Toward the Gram-positive bacteria tested thus far, the global cationic properties of sPLA2-IIA are necessary for optimal binding to intact bacteria and penetration of the multi-layered thick cell wall, but not for the degradation of membrane phospholipids that is essential for bacterial kill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
42
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 47 publications
1
42
0
1
Order By: Relevance
“…Since we have previously demonstrated that the sPLA 2 -X enzyme is increased in the airways of individuals with asthma (1, 2) and is increased with allergen challenge in humans and in mice, the homeostatic function of the enzyme should be considered, as lipid mediators have both pro-and antiinflammatory effects and the hydrolysis of membranes can directly lead to cell cytotoxicity. For example, other sPLA 2 s such as sPLA 2 -IIA, which we have also found to be elevated in the airways of asthmatics (3), have high activity against gram-positive bacteria due in part to its high net-positive charge, allowing for penetration of the bacterial cell wall (63,64). Although many of the sPLA 2 s have antibacterial properties, sPLA 2 -X is relatively unique because it acts strongly on the outer cell membrane of mammalian cells (65) and is generally thought to have less of a role on direct bacterial cytotoxicity (66).…”
Section: Discussionmentioning
confidence: 99%
“…Since we have previously demonstrated that the sPLA 2 -X enzyme is increased in the airways of individuals with asthma (1, 2) and is increased with allergen challenge in humans and in mice, the homeostatic function of the enzyme should be considered, as lipid mediators have both pro-and antiinflammatory effects and the hydrolysis of membranes can directly lead to cell cytotoxicity. For example, other sPLA 2 s such as sPLA 2 -IIA, which we have also found to be elevated in the airways of asthmatics (3), have high activity against gram-positive bacteria due in part to its high net-positive charge, allowing for penetration of the bacterial cell wall (63,64). Although many of the sPLA 2 s have antibacterial properties, sPLA 2 -X is relatively unique because it acts strongly on the outer cell membrane of mammalian cells (65) and is generally thought to have less of a role on direct bacterial cytotoxicity (66).…”
Section: Discussionmentioning
confidence: 99%
“…sPLA 2 act most efficiently by binding to PL-rich interfaces from which individual PL molecules can diffuse into the active site pocket of the bound enzyme, be degraded, and the products replaced by another PL substrate molecule from this interface (namely interfacial activation mechanism) (14,18). sPLA 2 , especially Group IIA, can penetrate through the cell wall of Grampositive bacteria to directly bind to the membrane, resulting in the high susceptibility of many Grampositive species (3). In contrast, Gram-negative bacteria exhibit much greater intrinsic resistance to sPLA 2 , which has been attributed to the unique structure of their additional outer envelope layer, the outer membrane (OM) (3,19).…”
mentioning
confidence: 99%
“…sPLA 2 , especially Group IIA, can penetrate through the cell wall of Grampositive bacteria to directly bind to the membrane, resulting in the high susceptibility of many Grampositive species (3). In contrast, Gram-negative bacteria exhibit much greater intrinsic resistance to sPLA 2 , which has been attributed to the unique structure of their additional outer envelope layer, the outer membrane (OM) (3,19). The OM of Gram-negative bacteria is arranged with an asymmetric lipid distribution: phospholipids (mainly phosphatidylethanolamine, PE) comprise the inner leaflet of the membrane, while the outer leaflet contains the complex glycolipid lipopolysaccharide (LPS).…”
mentioning
confidence: 99%
See 2 more Smart Citations